Supra‐subduction zone ophiolite from the Great Xing'an Range, China: Geochemistry, geochronology, and implication for formation in a back‐arc setting. Issue 5 (28th December 2021) - Shi, Zhiwei; Bai, Zhida; Dong, Guochen; Santosh, M.; Li, Liyang; Luo, Zhibo; Liu, Tao; Wang, Keqi
Abstract : Ophiolite provides key information on subduction–accretion processes along convergent plate margins. The Wunuer ophiolite in the Great Xing'an Range of NE China was considered to be an accreted fragment of the Palaeo‐Oceanic Plate. Based on field investigation, we evaluate the petrotectonic assemblages, geochemical features, and formation age of the ophiolite, which comprises gabbro, diabase, metabasalt, and radiolarian bedded chert with serpentinized amphibole‐pyroxene peridotites. Zircon U–Pb dating shows ages of 346 ± 6 Ma and 341 ± 6 Ma suggesting the timing of formation of the ophiolite as Early Carboniferous. The ophiolitic mafic rocks in Wunuer can be divided into two types based on their geochemical features. Type I is characterized by high Ti and low Al, with weakly negative Nb‐Ta and positive Pb anomalies and low light rare earth elements (LREE). These rocks display MORB‐like features, and correspond to partial melting product of depleted mantle. Type II has low Ti, high Al, notably negative Nb‐Ta and positive Pb anomalies, and is obviously enriched in LREE, large‐ion lithophile elements (LILE), and depleted in high‐field‐strength elements (HFSE), characterized by IAB‐like features, and may be formed by partial melting of more depleted mantle, which was strongly metasomatized by subduction fluids, resulted in high LILE/HFSE. The two types of ophiolites belong to SSZ type, obviously influenced by subduction, and their tectonic setting is inferred to be within a spreading ridge in a back‐arc basin. Combined with regional geological background, the Wunuer ophiolite probably represents a shrinking ocean basin and may be the late product of the long‐term and mature back‐arc basin, related to the terminal stage of ridge spreading within the back‐arc basin. Abstract : Both types of the mafic rocks in the Wunuer are SSZ type ophiolites with formation ages of 346 ± 6 Ma and 341 ± 6 Ma, and their tectonic setting is inferred to be spreading ridge within a back‐arc basin as the products of the late spreading ridge within a back‐arc basin.